2022
DOI: 10.1039/d2ta03441g
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancement in heterogeneous CO2 reduction processes in aqueous electrolyte

Abstract: Energy is essential in the human race toward prosperity and always remains in peak demand. Conventional fossil fuel may somehow fulfil this energy demand for now but at the cost...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 232 publications
(267 reference statements)
0
5
0
Order By: Relevance
“…is one of the most important research directions in future energy development programs. [1] As a novel generation of clean energy carriers, www.advancedsciencenews.com www.advenergymat.de Figure 1. Practical prospects for PV-driven water splitting: From device configurations to catalysts materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is one of the most important research directions in future energy development programs. [1] As a novel generation of clean energy carriers, www.advancedsciencenews.com www.advenergymat.de Figure 1. Practical prospects for PV-driven water splitting: From device configurations to catalysts materials.…”
Section: Introductionmentioning
confidence: 99%
“…is one of the most important research directions in future energy development programs. [ 1 ] As a novel generation of clean energy carriers, hydrogen energy has a high weight energy density (14.3 KJ kg −1 ) and offers a carbon‐free fuel. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%
“…Since the reduction potential values for different products are very close to each other, producing the desired product is thermodynamically challenging. 17 A number of these CRRs can yield CH 4 , CH 3 OH or C 2 H 4 , which is thermodynamically more favourable than the two-electron evolution reactions (Table 1). However, the kinetics of the CO 2 reduction is sluggish, mainly owing to the fact that the CO 2 ˙ − anion radical does not start to be formed up to −1.90 V in order to reform the linear molecule of CO 2 into a bent anion radical (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Recently, numerous reports were published on 2D Bi nanosheets (NS) having decent formate selectivity. 17–19 Nevertheless, synthesizing 2D metallic Bi NS with uniform heights is highly challenging, and direct synthesis requires an inert environment because of its low melting point and high susceptibility toward oxidation. 18 Furthermore, it is observed that after passing the potential with the maximum faradaic efficiency (FE), the FE of formate sharply drops at higher current density due to the mass transfer limitation of CO 2 , which also needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%